2014
DOI: 10.1051/0004-6361/201322938
|View full text |Cite
|
Sign up to set email alerts
|

Emission lines and shock waves in RR Lyrae stars

Abstract: Context. Emission lines observed in radially pulsating stars are thought to be produced by atoms de-exciting after being excited by a shock wave that is traveling into and then compressing, heating, and accelerating the atmospheric gas. Aims. With the help of recent observations, we examine the origin of all the different types of emission lines of hydrogen and helium that appear during a pulsation cycle. Methods. To analyze the physical origin of emission lines, we used the different models of atmospheric dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 32 publications
2
41
0
Order By: Relevance
“…Finally, because the shock is detached from the photosphere, the blueshifted emission component gradually disappears, and a P Cygni profile is formed. Gillet & Fokin (2014) suggested that the weak redshifted emission component occurring around the pulsation phase ϕ = 0.30 in RR Lyr can be also interpreted as a P-Cygni profile. The shock propagation toward the high atmosphere of the star could be the cause of this progressive and striking line profile change of the line profile.…”
Section: Physical Origin Of the D3 Helium P-cygni Profilementioning
confidence: 99%
See 4 more Smart Citations
“…Finally, because the shock is detached from the photosphere, the blueshifted emission component gradually disappears, and a P Cygni profile is formed. Gillet & Fokin (2014) suggested that the weak redshifted emission component occurring around the pulsation phase ϕ = 0.30 in RR Lyr can be also interpreted as a P-Cygni profile. The shock propagation toward the high atmosphere of the star could be the cause of this progressive and striking line profile change of the line profile.…”
Section: Physical Origin Of the D3 Helium P-cygni Profilementioning
confidence: 99%
“…If we assume that the D3 helium near the pulsation phase ϕ = 1.04 is built as a P-Cygni profile, then following Gillet & Fokin (2014), the shock front velocity is around 60 km s −1 . From the Hα profile Gillet & Fokin (2014) found that the shock velocity varies from 130 km s −1 at ϕ = 0.902 to 115 km s −1 at ϕ = 0.927.…”
Section: Physical Origin Of the D3 Helium P-cygni Profilementioning
confidence: 99%
See 3 more Smart Citations